Challenges of COVID-19: Preschool Teachers’ Views and Experiences During the Quarantine - Güneş, Gökhan; TORAN, MEHMET (İstanbul Kültür Üniversitesi, 2022)
The purpose of the study is to analyze the evidence gathered from the preschool teachers’ experiences during the COVID-19 pandemic quarantine. The study was carried out with 11 teachers who have professional experience ranging between 3 to 19 years from private and public preschools. The study was specified according to criterion sampling strategy under the purposeful sampling method. The data gathered via open-ended questions and the phenomenology method, one of the qualitative research designs, was used. The qualitative content analyses technique was applied for analyzing the data. It was reached remarkable themes about the preschool teachers’ pedagogical challenges during the COVID-19 pandemic based on the analysis of data. The themes and their subthemes are as follows: The theme “challenges in the distance education process” contains the sub-themes of children, teachers, and parents, the theme “views about educational policy in new normal” contains the sub-themes of technological infrastructure problems, unpreparedness, and negative attitudes, the theme “expectations for the improvement of distance education” contains the sub-themes of teacher training, effective family involvement activities, and technology-based programs.

Çalışmanın amacı, okul öncesi öğretmenlerinin COVID-19 salgını dönemi karantinasındaki deneyimlerinin incelenmesidir. Araştırma, özel ve resmi anaokullarından 3 ile 19 yıl arasında değişen mesleki deneyime sahip 11 öğretmen ile yürütülmüştür. Araştırmada yer alan katılımcılar, amaçlı örnekleme yöntemi kapsamında ölçüt örnekleme tekniğine göre belirlenmiştir. Çalışmada veri toplama aracı olarak açık uçlu görüşme soruları kullanılmıştır. Araştırmada nitel araştırma yöntemlerinden fenomenoloji yaklaşımı tercih edilerek verilerin analizinde içerik analizi tekniği kullanılmıştır. Çalışmada, okul öncesi öğretmenlerinin COVID-19 salgını sürecinde karşılaştıkları pedagojik zorlukları açıklayan dikkat çekici temalara ulaşılmıştır. Okul öncesi öğretmenlerinin karantina döneminde karşılaştığı zorlukları; “uzaktan eğitim sürecindeki zorluklar”, “yeni normalde eğitim politikasına ilişkin görüşler” ve “uzaktan eğitimin iyileştirilmesine yönelik beklentiler” temalarıyla ortaya koymaktadır. Genel temalardan uzaktan eğitim sürecindeki zorluklar; çocuk, öğretmen ve aile alt temalarından, yeni normalde eğitim politikasına ilişkin görüşler; teknolojik alt yapı eksikliği, hazırlıksız yakalanma ve olumsuz tutumlar alt temalarından ve uzaktan eğitimin iyileştirilmesine yönelik beklentiler genel teması da öğretmen eğitimi,etkili aile katılımı ve teknoloji temelli programlar alt temalarından oluşmaktadır.
COVID-19’un Zorlukları: Okul Öncesi Öğretmenlerinin Görüşleri ve Karantina Sırasındaki Deneyimleri
Keywords: Covid-19 Pandemic; Preschool Teacher; Quarantine Challenges; Early Childhood Education; Unpreparedness